Perilaku Wisata Generasi Z dalam Konstruksi Eksistensi Digital di Kota Bengkulu: Studi Fenomenologi - Mutiya, Merlen; Suminar, Panji; Himawati, Ika Pasca (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This study aims to understand how Generation Z in Bengkulu City interprets tourism activities as part of constructing their existence and identity in the digital space. This study uses a qualitative approach with a phenomenological design to explore the subjective experiences of informants in depth. The results show that Generation Z's tourism experience is not interpreted solely as a recreational activity, but as a multidimensional experience encompassing emotional needs for healing, strengthening social relations through togetherness, and the need for self-expression and recognition in the digital space. Exposure to visual content on social media acts as an initial stimulus that shapes destination interests and preferences, which are then subjectively processed based on the individual's emotional state and social needs before resulting in a travel decision. Documentation and content upload activities are an integral part of the tourism experience, as through this process informants receive social responses and validation.